PEMBARUAN PEMIKIRAN ISLAM INDONESIA: Negosiasi Intelektual Muslim dengan Modernitas - Mustofa, M. Lutfi (ULUL ALBAB Jurnal Studi Islam, 2011)
Renewal in Islam is an important part of the great tradition of Muslim community in their long life historical canvas. Initial dynamics of Islamic reform that appear along the modern era and in various areas, stretching from Saudi Arabia, Egypt, Turkey, India, North Africa, and Indonesia stressed that the context of modernity is demanding a revitalization of the Muslim intellectual heritage, including the works of earlier generations of Muslim scholars, as the role played by the European Christian community. As for the "second wave" of reform in Islam insists the appreciation of the importance of critical and historical approaches in understanding Islam, rather than theological, ideological, and political polemic. Therefore, to fill a more meaningful modernity Muslim reformers called for the need of refresher ijtihad by applying a new methodology to perform reinterpretation of sacred texts in solving social issues and contemporary morality.